DNMT3B Alleviates Liver Steatosis Induced by Chronic Low-grade LPS via Inhibiting CIDEA ExpressionSummary - Qiang Li; Wenjing Wang; Feifan Duan; Yaju Wang; Shuya Chen; Kangyun Shi; Yinyin Xia; Xinyu Li; Yu Gao; Guoquan Liu (Cellular and Molecular Gastroenterology and Hepatology, 2024)
Background & Aims: Nonalcoholic fatty liver disease is the most prevalent chronic liver disease and threats to human health. Gut dysbiosis caused by lipopolysaccharide (LPS) leakage has been strongly related to nonalcoholic fatty liver disease progression, although the underlying mechanisms remain unclear. Methods: Previous studies have shown that low-grade LPS administration to mice on a standard, low-fat chow diet is sufficient to induce symptoms of fatty liver. This study confirmed these findings and supported LPS as a lipid metabolism regulator in the liver. Results: Mechanically, LPS induced dysregulated lipid metabolism by inhibiting the expression of DNA methyltransferases 3B (DNMT3B). Genetic overexpression of DNMT3B alleviated LPS-induced lipid accumulation, whereas its knockdown increased steatosis in mice and human hepatocytes. LPS-induced lower expression of DNMT3B led to hypomethylation in promoter region of CIDEA, resulting in increased binding of SREBP-1c to its promoter and activated CIDEA expression. Hepatic interference of CIDEA reversed the effect of LPS on lipogenesis. These effects were independent of a high-fat diet or high fatty acid action. Conclusions: Overall, these findings sustain the conclusion that LPS is a lipogenic factor and could be involved in hepatic steatosis progression.